The Stressful Effects of Microplastics Associated With Chromium (VI) on the Microbiota of Daphnia Magna - Varg, Javier Edo; Bergvall, Christoffer; Svanbäck, Richard (Frontiers in Environmental Science, 2022)
Contamination by microplastics (particles < 1mm) is a growing and alarming environmental problem in freshwater systems. Evidence suggests that industrial effluents could be one of the critical point sources of microplastics and other pollutants, and their interaction can cause organismal stress and affect host and environmental microbial communities. We tested the individual and combined effects of microplastics and other pollutants on host survival and host associated (commensal) bacterial diversity. We exposed Daphnia magna to 1µm microplastic beads with a concentration of approximately 1820 particles/mL and chromium (VI) simultaneously with treatments of 2 and 5 ppm for 72 h. DNA extraction was done to amplify and sequence the ribosomal Bacterial 16S from both the water and the Daphnia. Daphnia experienced low mortality in treatments microplastics (13.3%) and 2ppm chromium VI (30%) individually. However, the combination of microplastics and 2ppm chromium (VI) increased the mortality to 74.4%. In the treatments with 5 ppm of chromium (VI) mortality rose to 100% after 30 hours of exposure. Microbial diversity changed in response to microplastics, chromium (VI), and both combined exposure. Microplastics and toxic metals can cause dysbiosis of freshwater environmental microbiota, whole host microbiota, and host survival. This work stresses the importance to assess how pollutants' individual and joint effects could affect organisms including their microbiome.